1859 Ind. Acts 129 - (:unkn) unknown (My University, 1859)
Ch. 78, § 1: Prohibited the wear or carry of any dirk, pistol, Bowie-knife, dagger, sword-cane, or any other dangerous or deadly weapon with the intent or avowed purpose of injuring another. Violators fined not exceeding five hundred dollars.
Keywords: CARRY - INTENT TO COMMIT CRIME